1994
DOI: 10.1093/rheumatology/33.12.1166
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Microvascular Responses in Lateral Epicondylitis

Abstract: The laser Doppler flowmeter, an instrument highly sensitive to changes in blood flow velocity in the dermal microvascular bed, was used to examine a sympathetic vasomotor response (SVR) in 40 patients with lateral epicondylitis. There was a significant association between the absence of a normal SVR in the skin overlying the affected enthesis compared with the unaffected contralateral epicondyle (P < 0.01). These results suggest that local dysfunction of the sympathetic nervous system may be associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 0 publications
0
30
0
2
Order By: Relevance
“…This is a drawback since nonsensory nerves may also influence the region. A sympathetic dysfunction has, for example, been suggested in the pathophysiology of tennis elbow, based on an abnormal response in dermal perfusion at the lateral epicondyle in tennis elbow patients [Smith et al, 1994]. The aim of the present study was to investigate the entire innervation at the ECRB tendinous origin at the lateral epicondyle.…”
Section: Introductionmentioning
confidence: 94%
“…This is a drawback since nonsensory nerves may also influence the region. A sympathetic dysfunction has, for example, been suggested in the pathophysiology of tennis elbow, based on an abnormal response in dermal perfusion at the lateral epicondyle in tennis elbow patients [Smith et al, 1994]. The aim of the present study was to investigate the entire innervation at the ECRB tendinous origin at the lateral epicondyle.…”
Section: Introductionmentioning
confidence: 94%
“…Finally, 1 study demonstrated an abnormal microvascular response of the skin overlying the painful epicondylar area, indicating a potential local dysfunction of the sympathetic nervous system. 22 Lateral epicondylalgia is undoubtedly a complex condition and it may be years before all questions are answered. However, we cannot ignore the current literature, which provides consistent evidence that there is an absence of an inflammatory component.…”
mentioning
confidence: 99%
“…It has been well proven by histologically that lateral epicondylitis or tennis elboe is not an acute inflammatory pathology, but instead it is failure of the normal tendon repair mechanism along with angiofibroblastic degeneration because tendons are relatively hypovascular. This hypovascularity may lead to hypoxic tendon degeneration which is main aetiology of tendinosis [3,24,25] . The traditional methods of treatment to treat tennis elbow, including rest, anti-inflammatory medications, bracing, physical therapy, iontophoresis, extra corporal shockwave, botulinum toxin, and corticosteroid injection, do not alter the tendon's poor healing properties secondary to poor vascularization of tendon, which is the basic pathophysiology in tennis elbow [1][2][3] .…”
Section: Discussionmentioning
confidence: 99%
“…But these therapies do not alter the common extensor tendon's poor healing properties secondary to poor vascularization of tendon, which is the basic pathophysiology in tennis elbow [3] . Hence these traditional therapies have shown inconsistent outcomes.…”
Section: Introductionmentioning
confidence: 99%